Marketing Strategy For Education Service To Increase Stakeholder Trust in TK Kemala Bhayangkari 16 Bantaeng - Moh Aris Pasigai; Zhella Pratiwi (Universitas Muhammadiyah Makassar, 2022)
This study aims to determine the Marketing Strategy of Educational Services at Kemala Bhayangkari 16 Kindergarten Bantaeng in terms of Increasing Stakeholders' Trust towards parents. The type of research used is the Qualitative Research Method. The data processed is the result of observations and interviews with the school of Tk Kemala Bhayangkari 16 Bantaeng as well as reports of new student admissions from the 2018 to 2021 school years. The data analysis technique used is descriptive analysis technique, which describes the data obtained from the Kemala Bhayangkari 16 Bantaeng Kindergarten is then associated with relevant theories by referring to the 4P concept of the marketing mix or marketing mix (Promotion, Place, Price, Person) and then concluded. Based on the results of data collection from the Kemala Bhayangkari 16 Bantaeng Kindergarten school, it can be concluded that the marketing strategy of educational services used in terms of increasing trust in users is by carrying out various kinds of promotions about schools through social media, distributing brochures to the general public, strengthening and adding relations with various media and friends, improve the quality and ability of educators and students